2013
DOI: 10.1146/annurev-med-050311-163404
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells: From Bench to Bedside

Abstract: Circulating tumor cells (CTCs) represent a surrogate biomarker of hematogenous metastases. In recent years, their detection has gained increasing interest. There is ample evidence regarding the ability to detect CTCs and their prognostic relevance, but their demonstrated predictive value in therapeutic response monitoring is clinically even more meaningful. Many clinical trials in the early and metastatic cancer setting now include CTCs as a monitoring parameter, and numerous translational studies attempting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 73 publications
0
61
0
Order By: Relevance
“…22 Other studies on both patients and animal models also suggest that increased cell number within tumor emboli is linked to higher metastasis rates and decreased recurrence-free survival. [4][5][6][7][8] Third, the whole tumor cluster may be easily trapped in vessels and form a metastatic focus, as evidenced by the endothelium-coated metastatic nodules in the livers and lungs of VETC 1 tumor-bearing mice. Therefore, the VETC pattern may provide an efficient novel metastasis mode that relies more on vascular pattern than on the migration and invasion activity of cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Other studies on both patients and animal models also suggest that increased cell number within tumor emboli is linked to higher metastasis rates and decreased recurrence-free survival. [4][5][6][7][8] Third, the whole tumor cluster may be easily trapped in vessels and form a metastatic focus, as evidenced by the endothelium-coated metastatic nodules in the livers and lungs of VETC 1 tumor-bearing mice. Therefore, the VETC pattern may provide an efficient novel metastasis mode that relies more on vascular pattern than on the migration and invasion activity of cancer cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Yunfei Yuan, 3 Rong-Ping Guo, 3 Wei-Hua Jia, 4 Jing-Ping Yun, 5 Min-Shan Chen, 3 Yaojun Zhang, 3 and…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this principle, high CTC numbers have been correlated with increased metastasis and decreased time to relapse, which supporting the predictive values on cancer progression, prognosis and survival in several cancers [3]. A meta-analysis of 49 eligible studies enrolling 6,825 breast cancer patients indicated CTC a stable prognostic biomarker at both earlyand metastatic stages [4].…”
mentioning
confidence: 75%
“…[1][2][3][4][5][6][7] The classical method for enumerating circulating cells is to draw small peripheral blood (PB) samples from the animals, which are subsequently analyzed with techniques such as flow cytometry, fluorescence microscopy, or more recently with microfluidic devices. [8][9][10][11][12] However, this "ex-vivo" approach is known to be fundamentally problematic, since handling, storage, and enrichment of PB samples have been shown to affect cell viability and behavior.…”
Section: Introductionmentioning
confidence: 99%